The linkages between private and public investments in Malaysia: the role of foreign direct investment - Choong, Chee Keong; Law, Siong Hook; Pek, Chuen Khee (Faculty of Economics and Management, Universiti Putra Malaysia, 2015)
The objective of this study is to investigate the linkages amongst private investment, government investments, foreign direct investment (FDI) and economic growth in the case of Malaysia. The results based on the cointegration test reveal that there is a single cointegrating vector in the system, which implies that private investment, government spending, FDI, economic growth and interest rate move together to achieve their steady state long run relationship. In addition, we find that both government spending and FDI have a positive effect on private investment and these two types of investments are “crowd in” private investments in the long run as well as in the short run.